Analysis of Fiscal Independence, Fiscal Dependence, and Fiscal Effectiveness of Central Lombok Regency 2019-2023 - Wulandari, Resty; Manan, Abdul; Fatimah, Siti (West Science Interdisciplinary Studies, 2024)
This study aims to analyze "fiscal independence, fiscal dependence, and fiscal effectiveness in Central Lombok Regency". The type of research used in this study is Descriptive research with a quantitative approach. The type of data used in the study is time series data. The data is analyzed using the Fiscal Independence Ratio, Fiscal Dependence Ratio, and Fiscal Effectiveness Ratio. The results of this study indicate that the Fiscal Independence of Central Lombok Regency in 2019-2023 shows a classification of "Not yet independent" with values of 11.04%, 11.55%, 8.95%, 12.21%, and 13.78%, then the Fiscal Dependence of Central Lombok Regency in 2019-2023 is in the "Very high" classification with values of 90.02%, 89.59%, 91.70%, 89.01%, and 87.78%, while the Fiscal Effectiveness of Central Lombok Regency in 2019-2023 shows a classification of "ineffective" with values of 9.51%, 9.83%, 7.73%, 10.80%, and 12.06%.